(untitled) (Journal of Bangladesh Academy of Sciences, 2017)
In this paper, we introduce five notions of level separation in T0 fuzzy bitopological spaces. We establish some relation among them. Also, we find relations between fuzzy topological spaces and corresponding fuzzy bitopological spaces in such spaces. Further, we prove that all these definitions satisfy good extension property. Finally, we prove that all these notionsare hereditary, productive and projective, moreover we observe that all concepts are preserved under one-one, onto and continuous mapping. Journal of Bangladesh Academy of Sciences, Vol. 41, No. 1, 57-68, 2017